Elaboración de una bebida con propiedades nutritivas a base de CHenopodium quinua willd (QUINUA), licor de cacao y sacarosa con distintas concentraciones - Arias Macías, Nataly Isabel (2018)
The objective of this work is a drink with nutritional properties based on quinoa, cocoa liquor and sucrose in the same way that it favors the eradication of child malnutrition and also helps in its industrialization. Encourage the preference for this food. By increasing consumption this grass would be able to open more market for producers who grow and market the best economy in the country, for this they apply a trifactorial design, A * B * C, where Factor A is the concentration of quinoa (100 ml , 115 ml, 125 ml); factor B the concentration of cocoa liquor (5 g and 10 g) and factor C is the concentration of sucrose (15 g and 20 g) with 12 treatments and 3 repetitions, giving a total of 36 experimental units formed by an approximate 250 ml For each sample packed for further analysis.Chemical and physical analysis was carried out among them Titratable acidity, soluble Solids, pH, Turbidity, Moisture, Ash was also carried out the organoleptic analysis evaluating the variables color, smell, taste, consistency, defect and acerptaility. The treatment that was differentiated from the others by its best results was a3 b2 c2 (250 mL of quinoa milk + 10 g of cocoa liquor + 20 g of sucrose) which provides as favorable results in Acidity (0.16%), Solids soluble (9.93), density (1.04g / cm3), turbidity (10.91NTU), pH (6.82), humidity (82.01%), ash (0.30%), the variables being acidity, pH , Moisture and ashes which does not represent difference with the other treatments. As for the organoleptic results, it obtained excellent acceptance with respect to odor, consistency, defects and acceptability as regards the other variables, it did not differ from the other treatments. Keywords: physical, Chemical, food, acceptance